(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Ovarian tumours are a leading cause of death in Bangladeshi women. Information about the clinical and pathological characteristics of ovarian tumours in Bangladesh is scanty. Present study aims to determine the correlation between clinical presentations and histopathological findings of suspected ovarian tumor patients admitted to a tertiary care hospital in Bangladesh. Materials and methods: Forty five women with ovarian mass scheduled for surgery were included in this prospective observational study from the Department of Obstetrics and Gynecology of Chittagong Medical College Hospital during the period 1st January to 30th June 2021. Demographic, clinical, and ultrasonograpy findings were collected by using a case record form. Histopathological diagnosis were collected following surgery and correlated with demographic, clinical and ultrasonography findings. Results: Out of 45 patients, 20 (44.4%) had benign and 25 (55.6%) had malignant ovarian tumours on histopathology and epithelial tumours presented in the majority of the cases (68.9%). The most frequent age group of presentation was 40-59 years in both benig (45%) and malignant (48%) groups. The predominant complaints of the patient were abdominal pain (73.3%) followed by abdominal lump (62%). Most patients (95.6%) presented with less than six months of symptoms, and postmenopausal status was the most frequent (52%) among the malignant tumour group. On ultrasonography, most benign and malignant cases (51.1%) had a tumour size of more than 10 cm. The majority of the tumours (91.1%) were unilateral, and (66.7%) were cystic in consistency. A significantly higher proportion of benign tumours were cystic than malignant tumours (95% vs 44%, p=0.001). Conclusion: The correct histopathological diagnosis of ovarian tumours is of prime importance, given their behavioural predictability, clinical correlation, and proper patient management. JCMCTA 2024 ; 35 (1) : 95-99